Distribusi Spasial Parameter Kualitas Air di Teluk Beno, Bali - Try Al Tanto; Rahmadi Prasetyo; Ilham Ilham (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2022)
ABSTRACTBy overviewing environmental issues and the pros/cons of the revitalization planning of the Benoa Bay, a study encompasing various problems is crucial to be carried out. One of which is related to the water quality. This study aims to spatially map the quality of seawater based on the values obtained from secondary data. Benoa Bay water quality conditions in 2016, has a water transparency ranging from 1.5-6 m, DO (not detected), the average of BOD was 47.49 mg/l, nitrate (0.2-0.3 mg/l), ammonia (0-0.33 mg/l), phenol (average 2.42 mg/l), and coliform (0-1100 MPN/100 ml). These values are alarming whereby it exceeds the quality standard allowed for marine biota. On the other hand, sea temperature ranged from 28.50 to 30.50°C, the average of pH was 8.27, salinity (31.6-32.8 ‰), sulfide (not detected), CN (not detected), oil fat (0-0.2 mg/l), and the average of TSS was 3.27 mg/l. These parameter concentrations are still suitable for supporting marine biota within Benoa Bay. Generally, the condition of water quality in Benoa Bay was categorized as polluted through the input of excess nutrients and bacteria. Keywords: sea water quality, physics, chemical, excess nutrient, biology, Benoa Bay, BaliABSTRAKMelihat permasalahan lingkungan yang terjadi, serta banyaknya pro dan kontra perencanaan revitalisasi Teluk Benoa, sebuah kajian untuk menjawab berbagai persoalan yang terjadi sangat perlu untuk dilakukan. Salah satu permasalahan tersebut berkaitan dengan kondisi kualitas perairan. Tujuan kajian ini adalah untuk memetakan kualitas air laut secara spasial berdasarkan nilai-nilai yang didapatkan dari data sekunder. Kondisi kualitas perairan Teluk Benoa pada tahun 2016, memiliki kecerahan perairan berkisar antara 1,5-6 m, DO (tidak terdeteksi), rata-rata nilai BOD sebesar 47,49 mg/l, nitrat (0,2-0,3 mg/l), amoniak (0-0,33 mg/l), phenol (rataan 2,42 mg/l), dan coliform (0-1100 MPN/100 ml). Konsentrasi parameter kaulitas air tersebut cukup mengkhawatirkan karena sudah melampaui rentang baku mutu air laut yang diperbolehkan untuk kehidupan biota laut. Disisi lain, parameter suhu berkisar antara 28,50-30,50°C, rata-rata nilai pH sebesar 8,27, salinitas (31,6-32,8 ‰), sulfida (tidak terdeteksi), CN (tidak terdeteksi), minyak lemak (0-0,2 mg/l), dan rata-rata TSS sebesar 3,27 mg/l), masih aman untuk kehidupan biota di sekitar perairan Teluk Benoa. Secara umum, kondisi kualitas perairan di Teluk Benoa termasuk dalam kategori tercemar melalui masukan nutrien berlebih dan bakteri.Kata kunci: kualitas air laut, fisika, kimia, nutrien berlebih, biologi, Teluk Benoa, Bali